2021
DOI: 10.1007/s11266-021-00415-w
|View full text |Cite
|
Sign up to set email alerts
|

Nonprofit Financial Resilience: Recovery from Natural Disasters

Abstract: Nonprofits operate in increasingly complex and turbulent environments. However, few studies have explored nonprofits’ resilience during natural disasters. This study uses Hurricane Katrina as a case study to explore whether nonprofits can regain their original financial performance after significant natural disasters and what organizational capacities and abilities influence their ability to bounce back. The results show that recovery is slow, taking between three and five years for half of the nonprofits in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 44 publications
1
5
0
Order By: Relevance
“…Regardless of their size or severity, disasters can undermine organizations’ growth and social performance. Therefore, nonprofits need to equip their resilience, which indicates companies’ capability to prepare (Fu and Lai 2021 ) and recover from disruption and perform (Chen 2021a , b ; Hutton et al 2021 ). Three types of capacity are social media communication, collaboration, and external communication essential in increasing humanitarian NGOs’ efficacy and efficiency in disaster risk sreduction operations.…”
Section: Bibliometric Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…Regardless of their size or severity, disasters can undermine organizations’ growth and social performance. Therefore, nonprofits need to equip their resilience, which indicates companies’ capability to prepare (Fu and Lai 2021 ) and recover from disruption and perform (Chen 2021a , b ; Hutton et al 2021 ). Three types of capacity are social media communication, collaboration, and external communication essential in increasing humanitarian NGOs’ efficacy and efficiency in disaster risk sreduction operations.…”
Section: Bibliometric Analysismentioning
confidence: 99%
“…By contrast, different capacities are needed in post-disaster recovery due to property damage, employee loss, and changes in the scope of their services. The most crucial capacities are financial and human resources to recover from the disaster (Chen 2021a , b ). However, most nonprofits do not have a financial reserve to recover and fail to develop sound procedures for recovering from staff losses, resulting in a drop in demand for their services.…”
Section: Bibliometric Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…In the context of a pandemic crisis, the concept of resilience appears even more crucial (Bhaskara & Filimonau, 2021 ; Lloyd-Smith, 2020 ). Studies have already shown that the resilience of the community around NPOs allows them to better weather the crisis (Paarlberg et al, 2020 ), but they remain anchored in a financial vision (Chen, 2021 ; Green et al, 2021 ; Kober & Thambar, 2021 ).…”
Section: Introductionmentioning
confidence: 99%